EFFECT OF GESTATIONAL DIABETES ON BLOOD SUGAR, LIVER AND RENAL FUNCTION TESTS - Khan, Radhia; Khan, Zakkia; Javed, Khalid; Ali, Khurshid (Journal of Ayub Medical College Abbottabad, 2012)
Objective: Type 2 diabetes adversely affects the liver and kidney function tests. This study was conducted to determine that either the liver and kidney functions are disturbed in the patients having gestational diabetes mellitus (GDM). Methods: One hundred and three women with GDM, and 97 healthy pregnant women (HPW) in their third trimester were registered in the Obs/Gyn Unit of Khyber Teaching Hospital, Peshawar in the time period Apr-Sep 2012. Blood sugar level, glycosylated haemoglobin status HbA1c, haemoglobin concentration, platelet count, liver function tests including alanine amino transferase (ALT), alkaline phosphatase (ALP) and bilirubin, renal function tests including urea and creatinine were determined. Results: Blood glucose level and HbA1c of GDM was significantly higher (p<0.001) than HPW. Fasting and random blood glucose and HbA1c of GDM and HPW were 110.90±9.10 vs 84.68±7.01 mg/dl, 148.53±7.21 vs 124.42±9.46 mg/dl and 6.49±1.20 vs 4.99±0.55 respectively. Haemoglobin percentage, platelet count, ALT, ALP, serum bilirubin and urea were not significantly different among the two groups. However, mean serum creatinine (0.82±0.32 mg/dl) in GDM was significantly higher (p<0.05) than in HPW (0.74±0.15 mg/dl). Conclusion: In gestational diabetes the LFTs may not be disturbed, however serum creatinine value is increased. Keywords: Gestational diabetes, HbA1c, liver function tests, urea, creatinine